FROM VIRAL TO VITAL: SOCIAL MEDIA AS A CATALYST FOR REPARATIVE JUSTICE AND COLLECTIVE HUMANITY - Viani, Adelia Marta (Sahabat Publikasi, 2023)
In the digital era, social media has emerged as a crucial public sphere where narratives of justice, solidarity, and activism transcend geographical and cultural boundaries. Movements such as Black Lives Matter, #MeToo, and #EndSARS demonstrate how viral content can spark global awareness of systemic injustice, yet questions remain on how such virality can transform into sustainable mechanisms of reparative justice. This study aims to explore how social media narratives transition from being merely viral to becoming vital in fostering reparative justice and collective humanity. Using a qualitative research design with a critical discourse approach, data were collected through digital content analysis of viral hashtags and complemented by in-depth interviews with activists, social media users, and scholars. Thematic analysis was employed to identify recurring patterns of collective memory, emotional validation, and solidarity in online spaces, while triangulation with existing literature strengthened the validity of findings. The study reveals three key findings: first, viral narratives play a pivotal role in raising collective awareness and archiving experiences of injustice; second, social media functions as a reparative arena where emotional validation and digital solidarity contribute to healing and resistance; and third, the transformation from viral to vital requires sustained narratives, hybrid online–offline mobilization, and ethical platform design oriented toward justice. These results contribute to developing the conceptual framework of